Note on transport equation and fractional Sumudu transform. - Kadem, Abdelouahab; Kilicman, Adem (Elsevier, 2011)
In this paper, the Chebyshev polynomials to solve analytically the fractional neutron transport equation in one-dimensional plane geometry are used. The procedure is based on the expansion of the angular flux in terms of the Chebyshev polynomials. The obtained system of fractional linear differential equation is solved analytically by using fractional Sumudu transform.